Visual Pedagogy of Religious Moderation: An Iconographic Analysis of Borobudur Reliefs - Nugroho, Muhammad Aji; Setyaningsih, Wahyu; Muna, Muhamad Khusnul (LPPM IAIN Kudus, 2026)
Although discussions on religious moderation are increasing worldwide, most studies still focus on theology or policy, and rarely consider visual and cultural sources. In this context, the reliefs of Borobudur Temple provide an important but often overlooked perspective. This study explores how religious moderation is expressed through the visual narratives found in these reliefs. Using a qualitative approach, it applies iconographic analysis, supported by interpretive readings of selected panels and relevant literature. The analysis highlights symbols, story patterns, and ethical meanings embedded in the reliefs. The findings show that Borobudur conveys key values of moderation, including tolerance, non-violence, compassion, cooperation, equality, and cultural integration, through visual narratives of ethical behavior and harmonious coexistence. More than just illustrations, these reliefs serve as a learning medium that shapes moral understanding. This study, therefore, introduces the idea of visual pedagogy of religious moderation and shows how cultural heritage can serve as a meaningful resource for religious education in today’s multicultural societies.